Information Systems Design and Intelligent Applications Proceedings of Third International Conference INDIA 2016, Volume 3 - Satapathy, Suresh Chandra; Mandal, Jyotsna Kumar; Udgata, Siba K.; Bhateja, Vikrant (Advances in Intelligent Systems and Computing,, 2016)
The third international conference on INformation Systems Design and Intelligent Applications (INDIA - 2016) held in Visakhapatnam, India during January 8-9, 2016. The book covers all aspects of information system design, computer science and technology, general sciences, and educational research. Upon a double blind review process, a number of high quality papers are selected and collected in the book, which is composed of three different volumes, and covers a variety of topics, including natural language processing, artificial intelligence, security and privacy, communications, wireless and sensor networks, microelectronics, circuit and systems, machine learning, soft computing, mobile computing and applications, cloud computing, software engineering, graphics and image processing, rural engineering, e-commerce, e-governance, business computing, molecular computing, nano-computing, chemical computing, intelligent computing for GIS and remote sensing, bio-informatics and bio-computing. These fields are not only limited to computer researchers but also include mathematics, chemistry, biology, bio-chemistry, engineering, statistics, and all others in which computer techniques may assist.